Fish diversity of Triyuga River, Udayapur District, Nepal - Shrestha, Jay Narayan (Our Nature, 2017)
The present paper deals with a synopsis of 48 fish species under 35 genera belonging to 17 families and 6 orders from Triyuga River. Some interesting fish species reported from this river are Barilus shacra, Garra annandalei, Psilorhynchoides pseudecheneis, Badis badis, Olyra longicoudata, Tor putitora, Labeo dero and Anguilla bengalensis. Fish diversity of Triyuga river is rich, thus further extensive study is essential for their conservation. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.